Urban mosques among high-rise: the issue of parking efficiency within compact urban settings - Utaberta, Nangkula; Mohd Sauffie, Nur Fatin; Chang, Sook Yee; Asif, Nayeem (Centre for Innovative Architecture and Built Environment (SErAMBI), Faculty Engineering and Built Environment, Universiti Kebangsaan Malaysia, 2018)
Car park facilities was one of the concerns in mosque design especially when the mosque is situated among dense high-rise buildings. High number of worshippers during Friday prayers has been leading to a huge demand of parking areas around the mosque. Insufficient of parking areas might result in illegal parking happen around the mosque and produces trouble to the local citizens. This study will study on the efficiency of the parking areas in and around the mosque in urban area.